GENDER DALAM PERBINCANGAN ISLAM DAN TRADISI LOKAL: Studi Penelusuran Karakteristik Wacana Gender Di Indonesia - Ach. Tijani; Mulyadi Mulyadi (PSGA LP2M IAIN Pontianak, 2018)
This study seeks to comprehensively review gender discourse in Islamic perspectives and local traditions. The gender discoursed in this study was examined through literature review and philosophical approaches. In the Islamic viewpoint, women are in a respectable position with equal distribution of rights and responsibilities with men. Likewise in the history of the locality of the Indonesian people, the position of women is also in a respectable position with their involvement in various lines of life, starting from the domestic sphere even Indonesian women are also actively involved in the socio-political sphere. As a result, gender discourse with various forms of protection in Indonesia is allegedly strongly exploited by global interests. [Kajian ini berupaya mengulas secara komprehensif wacana gender dalam perspektif Islam dan tradisi lokal. Wacana gender dalam kajian ini ditelaah melalui kajian kepustakaan dan pendekatan filosofis. Dalam sudut pandang keislaman perempuan berada pada posisi terhormat dengan pembagian hak dan kewajian secara berimbang dengan kaum laki-laki. Begitu juga dalam historistas kehdidupan lokalitas masyarakat Indonesia, posisi perempuan juga berada dalam posisi terhormat dengan keterlibatannya di berbagai lini kehidupan, mulai dari lingkup domestik bahkan perempuan Indonesia juga terlibat aktif di lingkup sosial-politik. Sebagai hasilnya, wacana gender dengan berbagai bentuk perlawannaya di Indonesia diduga kuat dieksploitasi oleh kepentingan global].